Benefits of a University Faculty-to-Faculty Mentoring Program - Anh Tran; Kay Gibson (The Advocate, 2016)
A faculty-to-faculty mentoring program is considered a useful way to help faculty be successful in teaching, research and service that lead to tenure attainment. Mentoring programs can be structured in a variety of ways, but usually the outcomes are focused on the benefits for mentees. This article presents a research study on a mentoring program in the College of Education at Wichita State University, in which mentors were tenured faculty and mentees were tenure–eligible. Through a written survey and an interview, participants identified perceived individual individual benefits of the mentoring program, and provided recommendations for future development. The traditional model of a mentoring program involves one mentor meeting with one mentee allowing for more individualized attention and greater rapport building (Reimers, 2014). According to researchers (Duranczyk, Madyun, Jehangir, & Higbee, 2011; Reimers, 2014), institutions should provide multiple types of mentoring. Types of mentoring include one-to-one, group, team, peer, and e-mentoring (Kwiatkowski, 2003; Reimers, 2014). Within each type, the program should allow for both informal and formal opportunities for mentoring to take place (America Psychological Association [APA], 2006; Ramani, Gruppen, & Krajic Kachur, 2006).